2016
DOI: 10.1097/hpc.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Risk Stratification and Management Pathway for Acute Chest Pain in the Emergency Department

Abstract: Objectives Chest pain is a common complaint in the emergency department, and a small but important minority represents an acute coronary syndrome (ACS). Variation in diagnostic workup, risk stratification, and management may result in underuse, misuse, and/or overuse of resources. Methods From July to October 2014, we conducted a prospective cohort study in an academic medical center by implementing a Standardized Clinical Assessment and Management Plan (SCAMP) for chest pain based on the HEART score. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Our search identified 778 citations (Figure ) and following removal of duplicates, we screened 557 studies, from which 62 studies underwent full‐text review. We included 29 distinct cohorts from 30 studies in the meta‐analysis . All included studies evaluated the prognostic accuracy of the HEART score using a low‐risk threshold (score between 0 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search identified 778 citations (Figure ) and following removal of duplicates, we screened 557 studies, from which 62 studies underwent full‐text review. We included 29 distinct cohorts from 30 studies in the meta‐analysis . All included studies evaluated the prognostic accuracy of the HEART score using a low‐risk threshold (score between 0 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies evaluated the HEART score for 30‐day incidence of MACE, while 13 evaluated the HEART score for 6‐week incidence of MACE . Most studies included only patients presenting with chest pain, while five studies included patients presenting with “suspected ACS.” In 14 studies, the ECG was interpreted by an ED physician, while in seven studies the ECG was specifically interpreted by a cardiologist . Four studies computed the HEART score using high‐sensitivity troponin assays, while the remaining studies used conventional troponin T or I assays (as used in the original study) …”
Section: Resultsmentioning
confidence: 99%
“…This indicates that there was nonadherence to the pathway, consistent with contemporary studies of pathway implementation. 4,5 Using multiple linear regression, a social work consult was associated with a 221.1 (95% CI; 116.4 – 325.8) minute increased EDLOS, indicating that nonadherence attenuated the maximum possible impact of the intervention on EDLOS.…”
Section: Discussionmentioning
confidence: 99%
“…When NIP processes are initiated, diagnostic results are finished sooner and disposition changes are improved (Hwang et al, 2016). Using a standardized NIP for CP can decrease LOS for CP patients in the ED (Baugh et al, 2016).…”
Section: Triage Nurse Ordersmentioning
confidence: 99%
“…Early completion of an EKG is essential for diagnosing ST-segment elevation myocardial infarction (STEMI), and EKG findings within 10 minutes of ED arrival are critical for positive outcomes (Yiadom, et al, 2017). EKG acquisition times found in the HEART study showed expedited patient care among intermediate and low risk CP patient populations while decreasing LOS (Baugh et al, 2016;Hwang et al, 2016). Safely determining the acuity of CP patients can also lead to early discharge among low-risk populations (Douma, et al, 2016;Mahler et al,…”
Section: Ekg Completionmentioning
confidence: 99%